TRENDS IN INTRINSIC WATER-USE EFFICIENCY OF NATURAL TREES FOR THE PAST 100-200 YEARS: A RESPONSE TO ATMOSPHERIC CO2 CONCENTRATION - O2, LIGHT AND HUMIDITY RESPONSES - Feng X. (My University, 1999)
To evaluate how the land carbon reservoir has been acting as a sink to the anthropogenic CO2 input to the atmosphere, it is important to study how plants in natural forests physiologically adjust to the changing atmospheric conditions. This has been studied intensively using controlled experiments, but it has been difficult to scale short-term observations to long-term ecosystem-level response. This paper derives variations of plant intrinsic water-use efficiency from natural trees for the past 100-200 years using carbon isotope chronologies. This parameter may potentially cause an increase in plant growth rate by improving the efficiency of plant water use, especially in arid environments. Attempts were made to isolate the variations of intrinsic water-use efficiency as a function of only the CO2 concentration of the atmosphere. The intrinsic water-use efficiency of almost all trees increased with increasing atmospheric CO2 concentration. This is caused by an increase in the carbon assimilation rate (A) and/or a decrease in the stomatal conductance (g). The increase in plant intrinsic water-use efficiency may imply an increase in plant transpiration efficiency which may have a direct connection with changes in plant biomass.